The Syntax-Semantics Interface Of Copular Constructions: Evidence From Standard Arabic - Al-Horais, Nasser (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This paper aims to provide additional supporting evidence for the Equative Approach by reducing the taxonomy of copular clauses into just two categories: predicational and equative. Data from copular structures in Standard Arabic are presented to bolster this approach. These data reveal that Standard Arabic features two distinct lexical copulas: (1) an inflected verbal copula,